Interaction between lactobacillus kefir and Saccharomyces lipolytica isolated from kefir grains: Evidence for lectin-like activity of bacterial surface proteins - Golowczyc, Marina Alejandra (2009)
Several microbial interactions involving yeast and lactobacilli have been suggested in fermented products. Co-aggregation between Lactobacillus kefir and yeast Saccharomyces lipolytica isolated from kefir grains was studied by scanning electron microscopy and aggregation assays. Six out of twenty Lb. kefir strains were able to co-aggregate with Sacch. lipolytica CIDCA 812 and showed thermolabile non-covalently bound surface molecules involved in this interaction. Co-aggregation inhibition after Lb. kefir pre-treatment with 5 m-LiCl or 20 g SDS/l showed that bacterial S-layer proteins play an important role in this interaction. Presence of different sugar (mannose, sucrose and fructose) or yeast pre-treatment with sodium periodate inhibited co-aggregation between Lb. kefir and Sacch. lipolytica. Co-aggregating Lb. kefir strains were also able to agglutinate with human red blood cells and they lost this ability after treatment with 5 m-LiCl. These results and the capacity of purified S-layer proteins of Lb. kefir to haemagglutinate, strongly suggest that a lectin-like activity of bacterial surface proteins (S-layer) mediates the aggregation with yeast cells.